Pengaruh Moralitas Individu Dan Religiusitas Terhadap Kecenderungan Kecurangan Dalam Pengelolaan Dana Desa (Studi Pada Pemerintah Desa Di Kabupaten Karawang) - Gani Sugani; Yana Mustika; Bella Puspita Audina (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to analyze the influence of individual morality and religiosity on fraud tendency in the management of village funds. Village funds play a crucial role in the development and welfare of communities at the village level but are often vulnerable to fraudulent practices that can hinder these objectives. This research employs a quantitative approach with a survey method involving 55 respondents who are involved in the management of village funds in several regions. The results of the study show that individual morality and religiosity significantly influence the tendency to commit fraud in the management of village funds. Partially, individual morality has a significant positive effect with a t-value of 2.095 and a significance level of 0.041. Religiosity also has a significant positive effect with a t-value of 5.005 and a significance level of 0.000. The simultaneous test (F test) shows that individual morality and religiosity together have a significant effect on fraud tendency, with an F-value of 25.028 and a significance level of 0.000. The coefficient of determination (Adjusted R²) of 0.471 indicates that the variables of individual morality and religiosity can explain 47.1% of the variability in fraud tendency. The remaining 52.9% is influenced by other factors.